Orientasi Pendidikan Dalam Perspektif Islam - Aminuddin Mamma (Al-Riwayah : Jurnal Kependidikan, 2015)
Trustee education programs should allow for self-direction and be customized to the schedules, needs, and preferred learning styles of individual trustees. While there is a common core of knowledge that all trustees should have, different trustees will select what they need to learn and will learn it in different ways. So, a variety of opportunities should be available, although all approaches should include time to discuss questions, principles, and applications. Right education leads to refinement of conduct. With refinement of behaviour, one’s life gets sublimated. Good intellect alone can lead happiness which is the source of peace. Proper education brings about association with good people. The company of the good is peace itself. Teachers are like guideposts. It is only when you play this role well that you will have done your duty by the boys and girls to divinise their lives. Although secular education may appear necessary for mundane existence, the importance of a spiritual basis for it should be recognised. However, the responsibility for imparting a spiritual orientation to education rests not only on teachers, but also on the parents as well as the authorities.